THE IMPACT OF MENTAL MODELS ON DEVELOPMENT AND RESTRUCTURING OF NATIONAL ECONOMIES - Pavel V. Zhuravlev; Irina V. Gorokhova; Olga N. Al'khimenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides a comparative analysis of different types of mental models in thinking activity, which determine economic functioning of society. By investigating overseas and home literature two key types were identified: non-western X -mentality and western Y -mentality. The authors show that these models of mentality both in historic and present day context determined and determine the essential parameters of development and restructuring of national economies. Based on the analysis of countries' economies they came to the conclusion about changing share of GDP in X - and Y -countries: the former became leaders in global GDP starting from the early 2000-s leaving behind the latter.